The boundaries of the state - Michael Wohlgemuth (Albert-Ludwigs-Universität Freiburg, Institut für Allgemeine Wirtschaftsforschung, Abteilung für Wirtschaftspolitik, 2011)
The paper is organized as follows: in part 2, I give a short account of Humboldt's boundaries of the state that relates to many present-day challenges to classical liberalism: his blunt rejection of any solicitude of the state for the positive welfare of the citizen which also covers education, religion and any kind of moral paternalism. In part 3, I refer to the new economic literature on the optimal size and number of nations in order to discuss whether small states are more likely to be (nearly) minimal states. This literature tends to disregard Humboldt's arguments in favour of exposing the individual to varieties of situations that he can choose and from which he can learn to self-develop. Therefore, in part 4, I argue that the evolutionary merits of this exposure can be illustrated by regarding institutional competition as a Hayekian discovery procedure. In part 5, I look at the partial removal of borders within the European Union and, using some intuitions from club theory, I argue that, in terms of the size of European government, integration has become in most areas too deep whereas in terms of the size of membership in the Union the EU has grown too big in some areas and too small in others. I conclude with a plea for more decentralization and competition amongst jurisdictions as a way to lead, as if by an invisible hand, to at least somewhat more limited states. My qualified claim is thus: more, and more open, boundaries between states lead to more limited governments.
Keywords: 330